Elucidating the mechanism of cardiac ischemia and reperfusion by proteomics approach - Xin, Li (2012)
To better understand the molecular basis of ischemia/reperfusion (I/R) injury, we assessed the temporal and quantitative alterations in the cardiac proteome of a mouse cardiac I/R model by iTRAQ approach at 30 minutes of ischemia, and at 60 or 120 mins reperfusion after 30 minutes ischemia using sham operation as the baseline control. Functions of the regulated proteins, Park7 and Ppia, were further studied in in vitro model by cell biological method and immunoprecipitation-MS approach. Secretome analysis was carried out by both iTRAQ and label free-based quantitative proteomics approaches on rat heart myoblast cell line subjected to 16 hr hypoxia and 24 hr reoxygenation. Large quantities of secreted proteins were identified. Further analysis on the modulated subproteome suggests that angiogenesis, inflammation, ECM remodeling including collagen deposition and cross-linking are regulated during hypoxia; while in subsequent reperfusion or re-oxygenation, proteins involved in anti-inflammation, ECM modulation are up-regulated and anti-apoptosis proteins are declined.